Places in Knots Remoteness and Connectivity in the Himalayas and Beyond - Saxer, Martin (Cornell University Press, 2023)
Tracing the experiences of mobile Himalayans across the globe, Places in Knots describes the ways in which Himalayan people relate to the multiple places they inhabit and the work and trouble of keeping their communities tied together. Martin Saxer describes global Himalayan ventures as a form of expansion of community rather than out-migration. Moving out does not sever the bonds of community. Instead, it is the pull that tightens the knot.Coffee-table books and trekking agencies continue to advertise the Himalayas as remote "hidden valleys," and NGOs see them as fragile mountain ecosystems to be protected from global forces of destruction. Places in Knots shows how these tropes of remoteness inform development and conservation policies and thus shape the contexts in which Himalayan connections with the wider world are forged and maintained. Following Himalayan journeys between valleys in Nepal and beyond, Saxer draws a picture of globalization that emerges not from the centers or below-but rather from the edge. Thanks to generous funding from LMU München, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other repositories.